The Maintenance of the Sasak Language in the Samawa Speech Community: A Case Study of Karang Anyar - Ramadhan, Eki Hizbi; Yusra, Kamaluddin; Putera, Lalu Jaswadi (Jurnal Ilmiah Profesi Pendidikan, 2025)
Social influence usually appears in people’s speech because language is closely related to the population in the place where the language is used. This research aims to explore the factors impacting language maintenance in the Sasak community at Karang Anyar hamlet. The method used was qualitative, it was conducted for two months, from January to February 2024. The subjects consisted of children to elderly people, aged 10 to 70 years old. The number of informants are 40 peoples. The data has been collected by some technique, including: observation, interview, audio recording and note taking. The instruments used are: observation sheet, interview questions, and audio recorder. The data collected by triangulation: observation, interview, and recording. The data were analysed through three stages namely: transcription, identification, and classification. The research result found that the maintenance of the Sasak language in Karang Anyar is still strong. There are more than two languages that are mastered by the majority of the residents. Sasak language is the most often used language in their daily life. Indonesian is only used in formal situation, namely: village office, post office, schools, and minimarkets. Sumbawa language used at certain moments, namely: a wedding event, circumcision event, and meeting at work place.